Effects of external loading on power output during vertical jumps: a comparison between water polo and volleyball players - Correa, S. C.; Ladeira, A. P. X.; Romano, R. G.; Guimaraes, G. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to compare results of the effects of external loading on power output during vertical jumps performed on a force platform by twelve male water polo athletes and ten female volleyball players. Peak power output was calculated from time-force curves during vertical jumps with and without external additional loads corresponding to 0%, 5%, 10% and 15 % of their body weight. The jumps were performed from a squat position, without lower limb counter-movement or arm swings. The results showed no significant differences in peak power output between the different loading conditions for volleyball athletes, but a significant difference between 0% and 10% loading conditions for water polo athletes. This study suggests that for both groups the load that generates maximum power output is body weight.